CLINICAL CHARACTERISTICS AND SURVIVAL OUTCOMES IN ACUTE MYELOID LEUKEMIA PATIENTS: SINGLE CENTER EXPERIENCE: Survival outcomes of acute myeloid leukemia patients - Virijević, Marijana; Pravdić, Zlatko; Cvetković, Mirjana; Trajković, Lazar; Pantić, Nikola; Sabljić, Nikica; Rajić, Jovan; Milošević, Violeta; Jaković, Ljubomir; Bogdanović, Andrija; Kraguljac-Kurtović, Nada; Jovanović, Jelica; et al. (Srpski medicinski časopis Lekarske komore, 2024)
Introduction/Aim: Acute myeloid leukemia (AML) is a heterogeneous disease, in terms of its biological characteristics and response to therapy. Numerous prognostic factors at diagnosis related to the disease itself, the treatment, and the response to treatment influence the outcome of AML. Despite the high rate of complete remission, overall survival (OS) is still poor. This study aims to determine the clinical and biological profile of patients with AML and its prognostic impact on the OS rate and disease-free survival (DFS).Materials and Methods: The retrospective analysis included 271 patients diagnosed with acute myeloid leukemia at the University Clinical Center of Serbia (UCCS) Hematology Clinic, between January 2018 and January 2023. Demographic parameters, the Eastern Cooperative Oncology Group performance status (ECOG PS), comorbidities, and the parameters of laboratory analysis and hematological diagnosis of AML were analyzed as potential risk factors for OS and DFS, using the univariate Cox regression model.Results: Out of a total of 271 patients, 206 (76%) were treated with intensive chemotherapy, of whom 108 were men and 98 were women. The average age of these respondents was 50.3 years. According to the European Leukemia Network (ELN) risk classification, the patients were mostly in the group with intermediate risk, i.e. 128 (62.1%) patients. The most common subtype of AML was AML NOS (AML not otherwise specified), present in 123 (59.7%) patients. Univariate analysis showed that age ≥ 60 years (p = 0.009) and WBC ≥ 30 x 109/l (p = 0.031) were unfavorable prognostic parameters for OS. AML subtype, MRC (myelodysplasia-related changes) was the most significant risk factor for shorter disease-free survival (p = 0.027).Conclusion: In the analyzed group of AML patients treated with intensive therapy, we demonstrated a low OS rate and showed that age and the MRC subtype of AML represent unfavorable risk factors for shorter OS and DFS, respectively.
Keywords: acute myeloid leukemia; prognostic factors; survival